2005
DOI: 10.1242/dev.01696
|View full text |Cite
|
Sign up to set email alerts
|

Cited2is required both for heart morphogenesis and establishment of the left-right axis in mouse development

Abstract: Establishment of the left-right axis is a fundamental process of vertebrate embryogenesis. Failure to develop left-right asymmetry leads to incorrect positioning and morphogenesis of numerous internal organs, and is proposed to underlie the etiology of several common cardiac malformations. The transcriptional modulator Cited2 is essential for embryonic development: Cited2-null embryos die during gestation with profound developmental abnormalities, including cardiac malformations, exencephaly and adrenal agenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 69 publications
4
97
0
Order By: Relevance
“…This is surprising since it is a well-known fact that human congenital cardiac malformations with bilaterally symmetric arrangement of the atrial appendages, so-called left and right atrial isomerism, are frequently associated with abnormal connections of the systemic and pulmonary venous tributaries (Uemura et al, 1996;Smith et al, 2006). During the past few years, genetic mouse models for left as well as right atrial isomerism have been used to analyze the role of L-R axis specification in the development of the venous heart pole (Liu et al, 2002;Anderson et al, 2004;Weninger et al, 2005;Hildreth et al, 2009). Analyses of Pitx2c-deficient mice, for example, have shown that this transcription factor, which normally is expressed only in the left half of the heart tube (Franco et al, 2000;Campione et al, 2001), suppresses a default program of sinus node formation in the left atrium (Mommersteeg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This is surprising since it is a well-known fact that human congenital cardiac malformations with bilaterally symmetric arrangement of the atrial appendages, so-called left and right atrial isomerism, are frequently associated with abnormal connections of the systemic and pulmonary venous tributaries (Uemura et al, 1996;Smith et al, 2006). During the past few years, genetic mouse models for left as well as right atrial isomerism have been used to analyze the role of L-R axis specification in the development of the venous heart pole (Liu et al, 2002;Anderson et al, 2004;Weninger et al, 2005;Hildreth et al, 2009). Analyses of Pitx2c-deficient mice, for example, have shown that this transcription factor, which normally is expressed only in the left half of the heart tube (Franco et al, 2000;Campione et al, 2001), suppresses a default program of sinus node formation in the left atrium (Mommersteeg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to PHD2 and FIH, CITED2 activation by hypoxia might indicate a role for this molecule in the rapid inactivation of the hypoxic response upon reoxygenation. CITED2 may play a role in heart morphogenesis and the establishment of left-right asymmetry in the early embryo (20)(21)(22).…”
mentioning
confidence: 99%
“…2 -binding protein (CBP)/p300 interacting transactivator with glutamic acid (Glu) and aspartic acid (Asp)-tail 2 (Cited2) is a multifunctional protein essential for mouse embryogenesis (1)(2)(3)(4). Embryos with a deletion of Cited2 have defects in multiple organs including the heart, liver, and adrenal glands and do not survive beyond E14.5 (1)(2)(3)(4).…”
Section: Crebmentioning
confidence: 99%
“…Embryos with a deletion of Cited2 have defects in multiple organs including the heart, liver, and adrenal glands and do not survive beyond E14.5 (1)(2)(3)(4). A knock-out of Cited2 in mice causes defects in arterial and ventricular septum and outflow tract, which are responsible for embryonic lethality of a Cited2 gene deletion (1,3,4). By interacting with hepatocyte nuclear factor 4␣, Cited2 regulates lipid and carbohydrate metabolism in embryos (2).…”
Section: Crebmentioning
confidence: 99%